Sahaabi Jabir bin Abdullah An analytical study - عبد اسماعيل قيس (Al-Adab Journal, 2018)
The personal Sahaabi Jabir bin Abdullah great personality, the pain of all the Islamic sciences from the understanding of the Koran and its interpretation and save it for conversations Prophet Muhammad was one of the companions the top in the number of Mroyate to talk of the Messenger of Allah (peace be upon him) and Mroyate for Ahlul Bayt (peace be upon them) . And raised (may Allah be pleased with him) in the hands of the Messenger of Allah (peace be upon him) it was a scientist solemn, jurist, up to date, and was at the forefront of modern companions from the Messenger of Allah (peace be upon him) narrated the many conversations in various jurisprudential doors and matters of law. It was (may Allah be pleased with him) fond of winning the flag and talk to the extent that he was pulling a backpacker in the request for the one talking, God and as a great companion to have a distinct life from the rest of the companions Bmlazemth to the Messenger of Allah (peace be upon him) and his prerogative to save many and varied conversations in the doors of Islamic law and taking Jabir bin Abdullah (may Allah be pleased with him) and a multitude of luck understanding of the Holy Quran and save it for the year, making it the Prophet’s noble character and solemnity of the status of the Companions of the Messenger of Allah (peace be upon him). Although the companion Jabir bin Abdullah (may Allah be pleased with him) was not so Commander feat referred to Mendez in the fighting but he was keen to participate in all invasions conquered the Messenger of Allah (peace be upon him) except invasions Badr and one to prevent him from his father before him. The Galilean companion Jabir bin Abdullah (may Allah be pleased with him) the most careful careful to reach out to every house and wooing them Recognizing and understanding of the verse: (Say No I ask him paid only in the affection of kinship)